Measurements of top-quark pair to Z-boson cross-section ratios at root s=13, 8, 7 TeV with the ATLAS detector - Çetin, Serkant Ali (SPRINGER, 2017)
Ratios of top-quark pair to Z-boson cross sections measured from proton-proton-collisions at the LHC centre-of-mass energies of root S = 13 TeV, 8 TeV, and 7 TeV are presented by the ATLAS Collaboration. Single ratios, at a given root S for the two processes and at different root S , for each process, as well as double ratios of the two processes at different root S , are evaluated. The ratios are constructed using previously published ATLAS measurements of the t (t) over bar and Z-boson production cross sections, corrected to a common phase space where required, and a new analysis of Z -> l(+)l(-) where l = e, mu at root S = 13 TeV performed with data collected in 2015 with an integrated luminosity of 3.2 fb(-1). Correlations of systematic uncertainties are taken into account when evaluating the uncertainties in the ratios. The correlation model is also used to evaluate the combined cross section of the Z -> e (+) e (-) and the Z -> mu (+) mu (-) channels for each value. The results are compared to calculations performed at next-to-next-to-leading-order accuracy using recent sets of parton distribution functions. The data demonstrate significant power to constrain the gluon distribution function for the Bjorken-x values near 0.1 and the light-quark sea for x < 0.02.
Keywords: Hadron-Hadron scattering (experiments)